Hours-of-Rest Regulations in the Canadian Shipping Industry - Buck, Leslie; Greenley, Michael; Loughnane, Dermot; Webb, Robert (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1996)
This paper discusses hours of rest for Canadian shipping employees on the basis of statutory regulations, the research literature, and consultations with representatives of the shipping industry during four workshops held in different parts of Canada. Topics include analyses of current regulations, operational practices and research on work and rest and on time of day and rest, and recommendations for change. The analyses found that current regulations do not distinguish between sleep and recreation during rest periods and fall to take into account time of day effects in relation to quality of sleep. The proposed changes in the regulations require the use of non-rotating 24-hour duty schedules providing for minimum rest periods and maximum work periods.